Dynamic response of a cable with triangular cross section subject to uniform flow at Reynolds number 3900 - Zhu, Hongbo; Ping, Huan; Wang, Rui; Bao, Yan; Zhou, Dai; Wei, Xuesen; Han, Zhaolong (Physics of fluids (1994), 2020)
The flow-induced vibrations of an infinite long flexible cable with a triangular cross section allowed to oscillate in the transverse direction are numerically investigated at a subcritical Reynolds number of 3900. The aim of the present investigation is to reveal the underlying mechanisms of galloping of a triangular cable via a highly resolved direct numerical simulation employing a high-order spectral/hp element method. Based on our previous results [Zhu et al., Phys. Fluids 31, 057101 (2019)], only one angle of attack in which one of the sides is facing the incoming flow, α = 60°, is studied in the present simulation. A tensioned beam model is employed to govern the dynamics of the triangular cable, and a tension value is selected to trigger a single wave along the cable. The numerical results show that the response amplitude of the triangular cable is significantly larger than that of a circular cable at the same conditions, i.e., the triangular cable vibration is more vigorous. Besides, the motion of the triangular cable can be divided into two independent types: the low frequency related to galloping and the high frequency related to vortex shedding. The first- and second-order turbulence statistics are also resolved to investigate the wake characteristics of a flexible body in a turbulent regime. The numerical results indicate that, as compared to the circular cable at the same conditions, more kinetic energy is transferred from the fluid to the triangular cable, which, in turn, is responsible for a lower turbulence intensity in the near wake (x/D < 10.0) of the cable.